2014
DOI: 10.1161/circinterventions.113.000949
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomographic Evaluation of Transplant Coronary Artery Vasculopathy With Correlation to Cellular Rejection

Abstract: Background-Cardiac allograft vasculopathy is an accelerated fibroproliferative process that affects the coronary arteries of transplanted hearts. Intracoronary imaging with optical coherence tomography enables detection of subangiographic cardiac allograft vasculopathy. Methods and Results-At the time of routine surveillance coronary angiography, 48 consecutive heart transplant recipients underwent optical coherence tomographic imaging of 1 coronary artery. Imaging findings were compared per rejection history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…In contrast, unique to our study is the fact that we also explored the relationship between rejection data and MPRi and GLS. While several previous studies have suggested a relationship between CAV and historical rejection episodes, these studies have not measured MPRi, and conflicting data exist regarding this relationship [35, 47–49]. With respect to GLS, several previous studies have noted an association between GLS and rejection [15, 18, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, unique to our study is the fact that we also explored the relationship between rejection data and MPRi and GLS. While several previous studies have suggested a relationship between CAV and historical rejection episodes, these studies have not measured MPRi, and conflicting data exist regarding this relationship [35, 47–49]. With respect to GLS, several previous studies have noted an association between GLS and rejection [15, 18, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Although CAV may develop at any stage after transplantation, events that occur during the first year, most likely arising from immunologically mediated injury to the vascular endothelium, appear to play an important role in CAV pathogenesis (7, 25). Previous studies have demonstrated an association of acute cellular rejection in the early post-transplant period with inflammatory plaque (increased necrotic core and dense calcium contents) and CAV progression late after heart transplantation (3, 7,12). Immunohistochemical studies also suggested that typical CAV lesions display a similar pattern of inflammatory changes when compared to the inflamed myocardium during acute cellular rejection (23,26).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies of native coronary atherosclerosis, vulnerable plaque does not always accompany severe coronary stenosis, and plaque rupture (or erosion) can occur even in patients with mild-to-moderate disease (29,30). Recent transplant studies also demonstrated the presence of silent plaque rupture and nonocclusive mural thrombi (suggestive of healed plaque rupture and/or erosion) late after transplantation (12,20,31). The present study extended these investigations, indicating that the thrombosis theory might also apply to CAV and that plaque instability could cause cardiac events regardless of significant coronary intimal thickening and/or negative vessel remodeling, suggesting plaque instability as an important independent risk factor for CAV progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations